IMPROVING THE JAPANESE LANGUAGE SKILLS OF YOUNG OKIAGARU FARMERS THROUGH HYBRID LEARNING METHOD FOR PREPARATION FOR AGRICULTURAL INTERNSHIP TO JAPAN IN CIPUTRI VILLAGE - Rahmawati, Yelni; Suharyati, Henny; Novita, Lina (Lembaga Pendidikan dan Penelitian Manggala Institute, 2024)
This community service program aims to enhance the language and cultural understanding of Okiagaru Farm’s young farmers, specifically through Japanese language training and Indonesian-Japanese cultural diplomacy. The training utilizes hybrid learning, combining synchronous Zoom sessions for real-time learning and asynchronous Google Classroom for independent study. By integrating tools like Canva for educational material design and utilizing Zoom for interactive lessons, the program has improved participants’ Japanese proficiency. Before training, students had minimal skills in grammar (10%), listening (15%), reading (5%), and conversation (10%). Post-training, there were significant improvements: grammar (75%), listening (80%), reading (70%), and speaking (80%). These improvements reflect not only the enhancement of language skills but also a deeper understanding of Japanese culture. This initiative has prepared participants for future internships in Japan and facilitated cultural exchange between Indonesia and Japan, fostering better diplomatic ties.